2021
DOI: 10.1155/2021/6648462
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Analysis of Record Statistic from the Inverse Weibull Distribution under Balanced Loss Function

Abstract: The main contribution of this work is to develop a linear exponential loss function (LINEX) to estimate the scale parameter and reliability function of the inverse Weibull distribution (IWD) based on lower record values. We do this by merging a weight into LINEX to produce a new loss function called weighted linear exponential loss function (WLINEX). We then use WLINEX to derive the scale parameter and reliability function of the IWD. Subsequently, we discuss the balanced loss functions for three different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The IW distribution was considered by Keller [14] to model failures of mechanical components subject to degradation. Afterward, many researchers studied the IW distribution, including, but not limited to, Calabria and Pulcini [15], Jiang et al [16], Mahmoud et al [17], Sultan [18], Kundu and Howlader [19], Hassan et al [20], Kumar and Kumar [21], and Al-Duais [22]. The random variable Y follows the two-parameter IW distribution, denoted by IW(θ, λ), if the corresponding PDF and CDF, are given by: g(y; θ, λ) = λθy −(θ+1) e −λy −θ , y ≥ 0, θ, λ > 0, (4) and G(y; θ, λ) = e −λy −θ , y ≥ 0, θ, λ > 0, (5) respectively, where θ > 0 is the shape parameter and λ > 0 is the rate parameter.…”
Section: Inverse Weibull Distribution and Its Entropy Indicesmentioning
confidence: 99%
“…The IW distribution was considered by Keller [14] to model failures of mechanical components subject to degradation. Afterward, many researchers studied the IW distribution, including, but not limited to, Calabria and Pulcini [15], Jiang et al [16], Mahmoud et al [17], Sultan [18], Kundu and Howlader [19], Hassan et al [20], Kumar and Kumar [21], and Al-Duais [22]. The random variable Y follows the two-parameter IW distribution, denoted by IW(θ, λ), if the corresponding PDF and CDF, are given by: g(y; θ, λ) = λθy −(θ+1) e −λy −θ , y ≥ 0, θ, λ > 0, (4) and G(y; θ, λ) = e −λy −θ , y ≥ 0, θ, λ > 0, (5) respectively, where θ > 0 is the shape parameter and λ > 0 is the rate parameter.…”
Section: Inverse Weibull Distribution and Its Entropy Indicesmentioning
confidence: 99%
“…Lemma 1. Suppose that T is the historical data information about the entropy function H. Then, under the SE loss function (25), the Bayesian estimator Ĥ1 for any prior distribution is shown in Equation ( 26):…”
Section: Bayesian Estimationmentioning
confidence: 99%
“…Mohammad and Sana [24] obtained the Bayes estimators and ML estimators for the unknown parameters of the IWD under lower record values. Faud [25] developed a linear exponential loss function, and estimated the parameter and reliability of the IWD based on lower record values under this loss function. Li and Hao [26] considered the estimation of a stress-strength model when stress and strength are two independent IWDs with different parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it offered simple but appealing large enough sample approximations to optimal timings, dubbed asymptotically pointwise optimal (APO) rules, and demonstrated that APO rules were asymptotically optimal (AO) under a second scenario. Many publications have examined the APO rule and how it might be used to address those other challenges [ 10 ]. Discrete-time events are the focus of the studies in these publications.…”
Section: Introductionmentioning
confidence: 99%
“…The LINEX loss function was officially created, and its properties were investigated further. It is a handy asymmetrical nonlinear function that increases dramatically on one end of zero and gradually on the other [ 15 ]. Much research has looked into estimating issues with LINEX loss function [ 16 ].…”
Section: Introductionmentioning
confidence: 99%